Kualitas Nata dari Kulit Melon dengan Perbedaan Varietas Melon (Cucumis melo L.) dan Macam Gula Berdasarkan Tebal, Berat dan Kadar Serat - Lely Hermawati; Utami Sri Hastuti; Agung Witjoro (Universitas Sebelas Maret, 2018)
Usually melon fruit consumed freshly or in the form of processed and the melon skin oftenly become wastes. An utilization of melon skin is by using fornata production. It is an alternative for waste reduction and food diversification. This research use two varieties of melon, i.e: Kanaya and Indorif. The sugar sort are: cane sugar, palm sugar and siwalan sugar. This research was done to (1) observe the effect of melon varieties towards nata qualities based on the thickness, weight, and fiber contents. (2) observe the effect sugar sorts towards nata qualities based on the thickness, weight, and fiber contents. (3) observe the effect of melon varieties and sugar sorts towards nata qualities based on the thickness, weight, and fiber contents. This research is an experimental research with factorial design. The research result shows: (1) There is no effect of melon varieties towards nata qualities based on the thick, weight, and fiber content, it is mean that the skin of Kanaya as well as Indorif melon could be useas material for nata production. (2) There is no effect of sugar sorts towards the natathickness. People can choose one of the three kinds of sugar for nata production. However, sugar sort are significantly affected towards the nata quality based on the weight and fiber content. The palm sugar have the highest weight and fiber content .(3) there is no interaction effect of melon varieties and sugar sorts towards the thickness and weight. However, the interaction of melon varieties and sugar sorts significantly affected towards the fiber content. The best nata quality best on fiber content is nata that made kanaya melon with palm sugar